Abdominal Panniculectomy Can Simplify Kidney Transplantation in Obese Patients - Promny, Dominik; Hauck, Theresa; Cai, Aijia; Arkudas, Andreas; Heller, Katharina M.; Wullich, Bernd; Apel, Hendrik; Horch, Raymund E.; Ludolph, Ingo (Urologia Internationalis, 2021)
Background: Obesity is frequently present in patients suffering from end-stage renal disease (ESRD). However, overweight kidney transplant candidates are a challenge for the transplant surgeon. Obese patients tend to develop a large abdominal panniculus after weight loss creating an area predisposed to wound-healing disorders. Due to concerns about graft survival and postoperative complications after kidney transplantation, obese patients are often refused in this selective patient cohort. The study aimed to analyze the effect of panniculectomies on postoperative complications and transplant candidacy in an interdisciplinary setting. Methods: A retrospective database review of 10 cases of abdominal panniculectomies performed in patients with ESRD prior to kidney transplantation was conducted. Results: The median body mass index was 35.2 kg/m(2) (range 28.5-53.0 kg/m(2)) at first transplant-assessment versus 31.0 kg/m(2) (range 28.0-34.4 kg/m(2)) at panniculectomy, and 31.6 kg/m(2) (range 30.3-32.4 kg/m(2)) at kidney transplantation. We observed no major postoperative complications following panniculectomy and minor wound-healing complications in 2 patients. All aside from 1 patient became active transplant candidates 6 weeks after panniculectomy. No posttransplant wound complications occurred in the transplanted patients. Conclusion: Abdominal panniculectomy is feasible in patients suffering ESRD with no major postoperative complications, thus converting previously ineligible patients into kidney transplant candidates. An interdisciplinary approach is advisable in this selective patient cohort.
CRIS-Team WoS Importer:2021-07-02

Air-Pressure-Supported Application of Cultured Human Keratinocytes in a Fibrin Sealant Suspension as a Potential Clinical Tool for Large-Scale Wounds - Sörgel, Celena; Schmid, Rafael; Kengelbach-Weigand, Annika; Promny, Theresa; Horch, Raymund E. (Journal of Clinical Medicine, 2022)
The treatment of large-scale skin wounds remains a therapeutic challenge. In most cases there is not enough autologous material available for full coverage. Cultured epithelial autografts are efficient in restoring the lost epidermal cover; however, they have some disadvantages, such as difficult application and protracted cell cultivation periods. Transplanting a sprayed keratinocyte suspension in fibrin sealant as biological carrier is an option to overcome those disadvantages. Here, we studied different seeding techniques regarding their applicability and advantages on cell survival, attachment, and outgrowth in vitro and thereby improve the cell transfer to the wound bed. Human primary keratinocytes were suspended in a fibrin sealant. WST-8 assay was used to evaluate the vitality for 7 days. Furthermore, the cells were labeled with CellTracker (TM) CM-Di-I and stained with a life/dead staining. Cell morphology, shape, and distribution were microscopically analyzed. There was a significant increase in vitality while cultivating the cells in fibrin. Sprayed cells were considerably more homogenously distributed. Sprayed cells reached the confluent state earlier than dripped cells. There was no difference in the vitality and morphology in both groups over the observation period. These findings indicate that the sprayed keratinocytes are superior to the application of the cells as droplets. The sprayed application may offer a promising therapeutic option in the treatment of large chronic wounds.
CRIS-Team WoS Importer:2022-09-16

Analysis of laboratory markers in body contouring procedures after bariatric surgery does not indicate particular risks for perioperative complications. - Stumpfe, Maximilian; Platzer, Juliane; Horch, Raymund E.; Geierlehner, Alexander; Arkudas, Andreas; Müller-Seubert, Wibke; Cai, Aijia; Promny, Theresa; Ludolph, Ingo (Perioperative Medicine, 2024)
BACKGROUND: Body contouring surgery after massive weight loss is associated with different risk factors. Wound healing disorders and seromas commonly occur postoperatively. Bariatric interventions lead to massive weight loss with excess skin and soft tissue. In this study, perioperatively collected laboratory markers of this special patient population were analyzed. METHODS: Fifty-nine patients were analyzed retrospectively regarding bariatric surgery, weight loss, body contouring surgery, laboratory markers, and complication rates. RESULTS: Body contouring surgery (n = 117) was performed in 59 patients. Weight loss was achieved after gastric bypass (40.1%), gastric banding (33.9%), or sleeve gastrectomy (26.0%), with an average of 69.2 kg. The most common body contouring procedure included abdominoplasty (n = 50), followed by thigh lift (n = 29), mammaplasty (n = 19), brachioplasty (n = 14), and upper body lift (n = 5). Analysis of laboratory markers revealed no exceptional and clinically relevant variations. Correlation analysis revealed associations between resection weight, amount of drain fluid, and particular laboratory markers. CONCLUSION: Analysis of perioperative laboratory markers in this special patient population after massive weight loss did not indicate clinically relevant risk factors regardless of the type of bariatric or body contouring surgery. Body contouring surgeries after bariatric interventions prove to be safe and low risk concerning perioperative laboratory markers and postoperative hospitalization.
EVALuna2:574369

An Innovative Arteriovenous (AV) Loop Breast Cancer Model Tailored for Cancer Research - An, Ran; Strissel, Pamela; Al-Abboodi, Majida; Robering, Jan Willem; Reakasame, Supachai; Eckstein, Markus; Peddi, Ajay; Hauck, Theresa; Bäuerle, Tobias; Boccaccini, Aldo R.; Youssef, Almoatazbellah; Sun, Jiaming; et al. (Bioengineering, 2022)
Animal models are important tools to investigate the pathogenesis and develop treatment strategies for breast cancer in humans. In this study, we developed a new three-dimensional in vivo arteriovenous loop model of human breast cancer with the aid of biodegradable materials, including fibrin, alginate, and polycaprolactone. We examined the in vivo effects of various matrices on the growth of breast cancer cells by imaging and immunohistochemistry evaluation. Our findings clearly demonstrate that vascularized breast cancer microtissues could be engineered and recapitulate the in vivo situation and tumor-stromal interaction within an isolated environment in an in vivo organism. Alginate–fibrin hybrid matrices were considered as a highly powerful material for breast tumor engineering based on its stability and biocompatibility. We propose that the novel tumor model may not only serve as an invaluable platform for analyzing and understanding the molecular mechanisms and pattern of oncologic diseases, but also be tailored for individual therapy via transplantation of breast cancer patient-derived tumors.
CRIS-Team Scopus Importer:2022-07-15
Keywords: animal model; arteriovenous loop; breast cancer

An In Vitro Approach for Investigating the Safety of Lipotransfer after Breast-Conserving Therapy - Promny, Theresa; Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kadam, Sheetal; Schmid, Rafael; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2022)
The application of lipotransfer after breast-conserving therapy (BCT) and irradiation in breast cancer patients is an already widespread procedure for reconstructing volume deficits of the diseased breast. Nevertheless, the safety of lipotransfer has still not been clarified yet due to contradictory data. The goal of this in vitro study was to further elucidate the potential effects of lipotransfer on the irradiated remaining breast tissue. The mammary epithelial cell line MCF-10A was co-cultured with the fibroblast cell line MRC-5 and irradiated with 2 and 5 Gy. Afterwards, cells were treated with conditioned medium (CM) from adipose-derived stem cells (ADSC), and the effects on the cellular functions of MCF-10A cells and on gene expression at the mRNA level in MCF-10A and MRC-5 cells were analyzed. Treatment with ADSC CM stimulated transmigration and invasion and decreased the surviving fraction of MCF-10A cells. Further, the expression of cytokines, extracellular, and mesenchymal markers was enhanced in mamary epithelial cells. Only an effect of ADSC CM on irradiated fibroblasts could be observed. The present data suggest epithelial–mesenchymal transition-like changes in the epithelial mammary breast cell line. Thus, the benefits of lipotransfer after BCT should be critically weighed against its possible risks for the affected patients.<br

Body Contouring Surgery Improves Physical Activity in Patients After Massive Weight Loss—a Retrospective Study - Maringa, Linda; Hauck, Theresa; Boos, Anja; Schmitz, Marweh; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background: The aim of the study was to compare physical activity (PA) in patients who had undergone massive weight loss (MWL), before and after body contouring procedures. Methods: All patients undergoing body contouring surgery after MWL between 2007 and 2017 with a minimum follow-up of 6 months after the last procedure were included in this retrospective study. Excluded were those with a body mass index > 35 kg/m2 and those with comorbidities leading to impaired PA. Quality of life (QOL) was assessed using the Moorehead-Ardelt QOL Questionnaire II. Evaluation of PA was obtained with the International Physical Activity Questionnaire (IPAQ) short form and the Freiburg PA Questionnaire. Functional impairment during exercise was analyzed using a self-designed functional impairment score (FIS). Results: In the 45 patients completing the survey (37 female, 8 male), an improvement in QOL (p < 0.001) and PA scored by the IPAQ (p = 0.017) was found. The Freiburg PA Questionnaire showed no difference in PA before and after body contouring surgery (p = 0,274). Furthermore, scores of the FIS indicated a decrease of functional impairment during physical activity after body contouring surgery (p < 0.001). Conclusion: Body contouring improves QOL and PA in patients after massive weight loss. The results of our study confirm the important role of plastic surgery in the treatment and maintenance of health of patients with former obesity.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Body contouring surgery; Massive weight loss; Physical activity; Quality of life

Childbearing and Pregnancy Trends among Female Plastic and Orthopedic/Trauma Surgeons in German-speaking Countries - Cai, Aijia; Horch, Raymund E.; Arkudas, Andreas; Müller-Seubert, Wibke; Promny, Theresa; Girard, Anna; Hameyer, Laura (Plastic and Reconstructive Surgery Global Open, 2025)
Background: Female surgeons face challenges when trying to balance family planning and surgical duties. Although US surgeons have been thoroughly investigated in terms of obstetric complications and perception toward pregnancy, information on surgeons in German-speaking countries is lacking. Methods: A multicentric online survey was conducted to analyze female plastic and orthopedic/trauma surgeons from Germany, and plastic surgeons from Switzerland and Austria. Results: Mean age during first pregnancy was 33 years. More than one-third of all surgeons intentionally postponed pregnancy for professional reasons. About one-third of the German surgeons was banned from clinical work during pregnancy, whereas 6% of all Swiss/Austrian surgeons were banned. Accordingly, the Swiss/Austrian surgeons were operating more often during pregnancy. Obstetric complications ranged from 41% to 58%. The Swiss/Austrian plastic surgeons had the lowest complication rate. The rate of cervical insufficiency was approximately 4%, which was higher than in the general and US surgeons' population, whereas fertility issues and miscarriage were lower in German-speaking plastic surgeons. Conclusions: Despite national maternity protection laws, obstetric complication rates of surgeons in German-speaking countries and the United States were similar. Cervical insufficiency was even more prevalent in the study population, which could be associated with an older age of the expectants. Therefore, those (strict) laws need to be reconsidered because a ban from surgery can lead to intentional postponement of pregnancy.
CRIS-Team Scopus Importer:2025-04-01

Corrigendum: Does indocyanine green fluorescence angiography impact the intraoperative choice of procedure in free vascularized medial femoral condyle grafting for scaphoid non-unions?(Front. Surg., (2022), 9, (962450), 10.3389/fsurg.2022.962450) - Mulica, Markus; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ludolph, Ingo (Frontiers in Surgery, 2023)
Incorrect Author Name In the published article, the authors namewere written asMulicaMarkus, Horch Raymund, Arkudas Andreas, Cai Aijia, Müller-SeubertWibke, Hauck Theresa and Ludolph Ingo The correct name order is (first name and surname). Markus Mulica, Raymund E. Horch, Andreas Arkudas, Aijia Cai, Wibke Müller- Seubert, Theresa Hauck, Ingo Ludolph Error in Figure Legend In the published article, there was an error in the legend for Figure 5 as published.
CRIS-Team Scopus Importer:2023-02-24
Keywords: free vascularized bone graft; indocyanine green angiography; medial femoral condyle bone graft; scaphoid non-union; union rate

Does indocyanine green fluorescence angiography impact the intraoperative choice of procedure in free vascularized medial femoral condyle grafting for scaphoid nonunions? - Mulica, Markus; Horch, Raymund E.; Andreas, Arkudas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ingo, Ludolph (Frontiers in Surgery, 2022)
Background: Free vascularized medial femoral condyle (MFC) bone grafts can lead to increased vascularity of the proximal pole and restore scaphoid architecture in scaphoid nonunions. The intraoperative perfusion assessment of the bone graft is challenging because the conventional clinical examination is difficult. Indocyanine green (ICG) angiography has previously been shown to provide a real-time intraoperative evaluation of soft tissue perfusion in reconstructive surgery. The present study investigated the utility of ICG angiography in patients treated with a free medial femoral condyle graft for scaphoid nonunions. Methods: We performed a retrospective analysis of patients with scaphoid nonunions, in which ICG angiography was used intraoperatively for perfusion assessment. The medical records, radiographs, intraoperative imaging, and operative reports of all patients were reviewed. Intraoperative ICG dye was administered intravenously, and laser angiography was performed to assess bone perfusion. The scaphoid union was examined using postoperative CT scans. Results: Two patients had documented osteonecrosis of the proximal pole at the time of surgery. Four patients received a nonvascularized prior bone graft procedure, and a prior spongiosa graft procedure was performed in one patient. The mean time from injury to the MFC bone graft surgery was 52.7 months, and the mean time from prior failed surgery was 10.4 months. Perfusion of the vascular pedicle of the MFC and the periosteum could be detected in all patients. In two patients, even perfusion of the cancellous bone could be demonstrated by ICG angiography. Following transplantation of the bone graft, patency of the vascular anastomosis and perfusion of the periost were confirmed by ICG angiography in the assessed cases. No additional surgery regarding a salvage procedure for a scaphoid nonunion advanced collapse was necessary for the further course. Conclusion: ICG-angiography has shown to be a promising tool in the treatment of scaphoid nonunion with medial femoral condyle bone grafts. It enables intraoperative decision making by assessment of the microvascular blood supply of the periosteum and the vascular pedicle of the MFC bone graft. Further studies need to evaluate the impact on union rates in a long-term follow-up.
CRIS-Team Scopus Importer:2022-09-30
Keywords: free vascularized bone graft; indocyanine green angiography; medial femoral condyle bone graft; scaphoid nonunion; union rate

Glomustumor am Finger – eine seltene, aber schmerzhafte handchirurgische Entität - Promny, Dominik; Horch, Raymund E.; Agaimy, Abbas; Hauck, Theresa (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2020)
CRIS-Team WoS Importer:2020-07-10

Growth factors IGF-1 and KGF and adipose-derived stem cells promote migration and viability of primary human keratinocytes in an in vitro wound model - Stadelmann, Nina; Horch, Raymund E.; Schmid, Rafael; Ostendorf, David; Peddi, Ajay; Promny, Theresa; Boos, Anja; Kengelbach-Weigand, Annika (Frontiers in Medicine, 2025)
Introduction: In the field of plastic surgery, epidermal transplantation is a potential treatment for chronic wounds that results in only minor donor site morbidity. Improving the regenerative capacities of epidermal grafts or single-cell suspensions and therefore accelerating healing processes would be of significant interest. Methods: In the present study, we analyzed the effects of growth factors and adipose-derived stem cells (ADSCs) on keratinocyte properties. For optimum translation into the clinical setting, primary human keratinocytes and patient-matched ADSCs were isolated and used in an in vitro wound model. Results: The keratinocyte migration and viability increased after treatment with the growth factors insulin-like growth factor 1 (IGF-1) and keratinocyte growth factor (KGF). A similar effect was observed with the use of a concentrated ADSC-conditioned medium (ADSC-CM). It was further possible to isolate the keratinocytes in a xenogen-free medium, which is essential for clinical translation. Importantly, a patient-dependent influence on the effects of the growth factors and ADSC-CM was observed. Discussion: This study provides potential for the improvement of epidermal transplantation in the treatment of chronic wounds using xenogen-free isolated and cultivated keratinocytes, growth factors, and ADSC. Translating these results into clinical application may help accelerate wound healing and shorten the time until patients can return to everyday life.
CRIS-Team Scopus Importer:2025-02-28
Keywords: adipose-derived stem cells; conditioned medium; growth factors; keratinocytes; wound healing

Improving the Safety of DIEP Flap Transplantation: Detailed Perforator Anatomy Study Using Preoperative CTA† - Frank, Katharina; Stroebel, Armin; Ludolph, Ingo; Hauck, Theresa; May, Matthias; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Journal of Personalized Medicine, 2022)
Background: Deep inferior epigastric perforator and muscle sparing transverse rectus abdominis muscle flaps are commonly used flaps for autologous breast reconstruction. CT-angiography allows to analyse the perforator course preoperatively. Our aim was to compare the different aspects of perforator anatomy in the most detailed study. Methods: CT-angiographies of 300 female patients with autologous breast reconstruction of 10 years were analysed regarding the anatomy of the deep inferior epigastric artery and every perforator. Results: Overall, 2260 perforators were included. We identified correlations regarding the DIEA branching point and number of perforators and their intramuscular course. The largest perforator emerged more often from the medial branch of the DIEA than the smaller perforators (70% (416/595) vs. 54% (878/1634), p < 0.001) and more often had a direct connection to the SIEV (large 67% (401/595) vs. small 39% (634/1634), p < 0.01). Medial row perforators were larger than the laterals (lateral 1.44 mm ± 0.43 (n = 941) vs. medial 1.58 mm ± 0.52 (n = 1304) (p < 0.001)). The larger and more medial the perforator, the more likely it was connected to the SIEV: perforators with direct connection to the SIEV had a diameter of 1.65 mm ± 0.53 (n = 1050), perforators with indirect connection had a diameter of 1.43 ± 0.43 (n = 1028), perforators without connection had a diameter of 1.31 mm ± 0.37 (n = 169) (p < 0.001). Medial perforators were more often directly connected to the SIEV than lateral perforators (medial 56% (723/1302) vs. lateral 35% (327/941), p < 0.001). A lateral perforator more often had a short intramuscular course than medial perforators (69% (554/800) vs. 45% (474/1055), p < 0.001), which was also more often observed in the case of a small perforator and a caudal exit of the rectus sheath. Conclusion: The largest perforator emerges more often from the medial branch of the DIEA and frequently has a direct connection to the SIEV, making medial row perforators ideal for DIEP flap transplantation.
CRIS-Team Scopus Importer:2022-06-10
Keywords: autologous breast reconstruction; CTA; DIEP flap; MS-TRAM flap; perforator

Influence of the autotaxin-lysophosphatidic acid axis on cellular function and cytokine expression in different breast cancer cell lines - Hauck, Theresa; Kadam, Sheetal; Heinz, Katharina; Garcia Peraza, Maria; Schmid, Rafael; Kremer, Andreas; Wolf, Katharina; Bauer, Alina; Horch, Raymund E.; Arkudas, Andreas; Kengelbach-Weigand, Annika (Scientific Reports, 2022)
Previous studies provide high evidence that autotaxin (ATX)-lysophosphatidic acid (LPA) signaling through LPA receptors (LPAR) plays an important role in breast cancer initiation, progression, and invasion. However, its specific role in different breast cancer cell lines remains to be fully elucidated to offer improvements in targeted therapies. Within this study, we analyzed in vitro the effect of LPA 18:1 and the LPAR1, LPAR3 (and LPAR2) inhibitor Ki16425 on cellular functions of different human breast cancer cell lines (MDA-MB-231, MDA-MB-468, MCF-7, BT-474, SKBR-3) and the human breast epithelial cell line MCF-10A, as well as Interleukin 8 (IL-8), Interleukin 6 (IL-6) and tumor necrosis factor (TNF)-alpha cytokine secretion after LPA-incubation. ATX-LPA signaling showed a dose-dependent stimulatory effect especially on cellular functions of triple-negative and luminal A breast cancer cell lines. Ki16425 inhibited the LPA-induced stimulation of triple-negative breast cancer and luminal A cell lines in variable intensity depending on the functional assay, indicating the interplay of different LPAR in those assays. IL-8, IL-6 and TNF-alpha secretion was induced by LPA in MDA-MB-468 cells. This study provides further evidence about the role of the ATX-LPA axis in different breast cancer cell lines and might contribute to identify subtypes suitable for a future targeted therapy of the ATX-LPA axis.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Cancer; Medical research; Molecular medicine

Novel imaging methods reveal positive impact of topical negative pressure application on tissue perfusion in an in vivo skin model - Müller-Seubert, Wibke; Roth, Sascha; Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo (International Wound Journal, 2021)
The influence of topical negative pressure application (TNPA) on tissue perfusion still remains controversial. TNPA was applied for 30 minutes on intact skin of 21 healthy participants. Measurements of tissue oxygen saturation and tissue temperature as signs of tissue perfusion were performed before application of the TNPA, directly after removal of the TNPA and 5, 10, 15, 20, and 30 minutes after removal of the dressing using the near infrared imaging (NIRI) and a thermal imaging camera. Tissue oxygen saturation showed an increase from 67.7% before applying the TNPA to 76.1% directly after removal of TNPA, followed by a decrease of oxygen saturation 30 minutes after removal of TNPA. The measured temperature of the treated skin area increased from 32.1 degrees C to 36.1 degrees C after removal of TNPA with a consecutive decrease of the temperature 30 minutes after removal. TNPA resulted in both a higher tissue oxygen saturation and a higher skin temperature after 30 minutes compared to the beginning. TNPA increases both tissue oxygen saturation and skin temperature as sign of an increase of tissue perfusion. NIRI and thermal imaging proved to be useful for measuring changes in tissue perfusion.
CRIS-Team WoS Importer:2021-06-25

Operating on the Edge? Body Contouring Procedures in Patients with Body Mass Index Greater 35 - Hauck, Theresa; Schmitz, Marweh; Horch, Raymund E.; Arkudas, Andreas; Boos, Anja; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background Body contouring surgery after massive weight loss was shown to ameliorate the patient's quality of life and to enhance physical and psychological well-being. However, numerous patients are still obese when presenting for body contouring surgery, not able to lose additional weight for various reasons. Data regarding general feasibility, outcome, and postoperative complications in obese patients is rare. The aim of this study was to investigate the outcome in body contouring procedures in obese patients.
CRIS-Team WoS Importer:2019-05-24

Palmar dislocation of the proximal interphalangeal joint and traumatic boutonnière deformity - Hauck, Theresa; Müller-Seubert, Wibke; Horch, Raymund E. (Unfallchirurg, 2017)
Injury to the central slip of the extensor tendon may occur with open and also with closed injuries, such as volar dislocation of the proximal interphalangeal (PIP) joint. For adequate treatment, it is necessary to identify all injured structures. Without appropriate primary management, the patient is likely to develop a subacute to chronic posttraumatic boutonnière deformity. A fixed boutonnière deformity requires recovery of joint mobility. Once joint mobility is achieved, secondary surgical reconstruction of the central slip can be performed with a tendon transfer or a tendon transplant.
EVALuna2:32836

Paradoxical Perfusion Reaction of the contralateral Hand after Hand MRI - Promny, Dominik; Grüner, Jasmin; Hauck, Theresa; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2022)
Aufgrund der Fähigkeit, die komplexe Anatomie der Hand und des Handgelenks detailliert abzubilden, ist die Magnetresonanztomografie (MRT) ein ideales bildgebendes Verfahren für die Analyse vieler unterschiedlicher Traumata und Pathologien. Die MRT wird häufig nach initialer Röntgen- und Ultraschalldiagnostik ergänzend durchgeführt. Zuletzt erfolgten pro Jahr ca. 10 Millionen MRT-Untersuchungen in Deutschland [1]. Zu den häufigsten Indikationen für die Durchführung einer MRT-Untersuchung der Hand zählen: Beurteilung der intrinsischen Bänder des Handgelenks und des triangulären fibrokartilaginären Komplexes (TFCC), Charakterisierung von Raumforderungen (z. B. Ganglien oder Weichteiltumore), Detektion von Beuge- und Strecksehnenverletzungen und Kapsel-/Bandläsionen an den Fingern sowie Nachweis okkulter Knochenverletzungen [2], [3], [4]. Damit die Anatomie der einzelnen Strukturen der Hand bestmöglich abgebildet wird und Bewegungsartefakte möglichst gering gehalten werden können, erfordert dies eine Optimierung der Platzierung der Hand in der gewählten Spule sowie der Bildgebungsparameter (u. a. Schichtdicke, Sichtfeld und Repetitionszeit/Echozeit). Regulär werden Patienten in Bauchlage mit über dem Kopf ausgestrecktem Arm in der „Superman“-Position gelagert, sodass die Hand für eine bestmögliche, homogene Bildqualität im Isozentrum des Magnetfelds positioniert wird. Dies ist jedoch für manche Patienten unangenehm, und einige Patienten sind nicht im Stande, die MRT-Untersuchung in dieser Lagerung zu vollenden [5]. Im Folgenden berichten wir über einen außergewöhnlichen Fall, bei dem es im Rahmen einer MRT-Untersuchung der rechten Hand zu einer relevanten Veränderung der Perfusionsverhältnisse an der linken Hand gekommen war, bei vorausgegangener „Superman“-Lagerung während der MRT-Untersuchun
CRIS-Team WoS Importer:2022-03-04

Postbariatrische plastische Körperrekonstruktionen - Promny, Theresa; Ludolph, Ingo; Müller-Seubert, Wibke; Cai, Aijia; Promny, Dominik; Horch, Raymund E. (Die Chirurgie, 2024)
Massive weight loss following bariatric surgery is often accompanied by functional impairments due to the resulting excess skin and soft tissues. To achieve both functional reconstruction and restoration of the body silhouette, it is imperative to undergo body contouring surgery involving the strategic transposition of tissues. Several surgical techniques are available for the affected body regions and their application for treatment is determined by the unique circumstances specific to each patient. When conducted by skilled practitioners, postbariatric body reconstruction can be executed safely, leading to outcomes that are both functionally and esthetically satisfying, ultimately contributing to an enhanced quality of life for patients. This article provides the fundamental principles for patient selection, surgical preparation, treatment planning, surgical techniques and the postoperative care following bariatric surgery.
EVALuna2:574356

Projection Mapping for In-Situ Surgery Planning by the Example of DIEP Flap Breast Reconstruction - Martschinke, Jana; Klein, Vanessa; Kurth, Philipp; Engel, Klaus; Ludolph, Ingo; Hauck, Theresa; Horch, Raymund E.; Stamminger, Marc (Eurographics Workshop on Visual Computing for Biology and Medicine, 2021)
Nowadays, many surgical procedures require preoperative planning, mostly relying on data from 3D imaging techniques like computed tomography or magnetic resonance imaging. However, preoperative assessment of this data is carried out on the PC (using classical CT/MR viewing software) and not on the patient's body itself. Therefore, surgeons need to transfer both their overall understanding of the patient's individual anatomy and also specific markers and labels for important points from the PC to the patient only with the help of imaginative power or approximative measurement. In order to close the gap between preoperative planning on the PC and surgery on the patient, we propose a system to directly project preoperative knowledge to the body surface by projection mapping. As a result, we are able to display both assigned labels and a volumetric and view-dependent view of the 3D data in-situ. Furthermore, we offer a method to interactively navigate through the data and add 3D markers directly in the projected volumetric view. We demonstrate the benefits of our approach using DIEP flap breast reconstruction as an example. By means of a small pilot study, we show that our method outperforms standard surgical planning in accuracy and can easily be understood and utilized even by persons without any medical knowledge.

Response to the letter to the editor ‘Novel imaging methods reveal positive impact of topical negative pressure application on tissue perfusion in an in-vivo skin model’ - Müller-Seubert, Wibke; Roth, Sascha; Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo (International Wound Journal, 2021)
CRIS-Team Scopus Importer:2021-09-17

Secondary breast reconstruction after mastectomy using the DIEP flap - Hauck, Theresa; Horch, Raymund E.; Schmitz, Marweh; Arkudas, Andreas (Surgical Oncology-Oxford, 2018)
INTRODUCTION: Breast reconstruction is an important element in the successful therapy of breast cancer [1]. Thereby, autologous microvascular breast reconstruction has been shown to be a reliable technique. The use of a deep inferior epigastric perforator (DIEP) flap or a muscle-sparing (MS) free transverse rectus abdominis musculocutaneous (TRAM) flap is recognized in many centres as gold standard for reconstructive options [2-4]. Based on our experiences with 137 patients over a 5-year period we want to highlight the technical aspects of the free microsurgical autologous breast reconstruction using a DIEP flap. PATIENTS AND METHODS: Between 01/2013 and 12/2017 we treated 137 patients (age 32-78 years, mean age 52 years) after mastectomy with autologous microsurgical free flap breast reconstruction. A DIEP flap was used for breast reconstruction in 33 patients. In 104 cases, we performed a muscle sparing TRAM flap. In this video we demonstrate the typical sequence of operative steps of a DIEP flap in a 32 year old patient after mastectomy due to an invasive ductal breast carcinoma. RESULTS: The rate of total flap loss in our department was 2.2% including all patients. In less than 1%, partial flap necrosis could be observed. 61% of the patients had undergone previous irradiation. Within the small number of flap loss, we could not observe a trend towards a correlation between flap loss and previous irradiation. CONCLUSION: Autologous breast reconstruction using a DIEP or MS-TRAM flap provides a surgically safe technique including a low incidence of flap loss in specialized centres.
EVALuna2:211470

The Effect of Ionizing Irradiation on the Autotaxin-Lysophasphatidic Acid Axis and Interleukin-6/8 Secretion in Different Breast Cancer Cell Lines - Promny, Theresa; Scherrer, Isabell; Kadam, Sheetal; Schmid, Rafael; Jost, Tina; Distel, Luitpold; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2024)
Background: The Autotaxin (ATX)-lysophosphatidic acid (LPA) axis is involved in decreasing radiation sensitivity of breast tumor cells. This study aims to further elucidate the effect of irradiation on the ATX-LPA axis and cytokine secretion in different breast cancer cell lines to identify suitable breast cancer subtypes for targeted therapies. Methods: Different breast cancer cell lines (MCF-7 (luminal A), BT-474 (luminal B), SKBR-3 (HER2-positive), MDA-MB-231 and MDA-MB-468 (triple-negative)) and the breast epithelial cell line MCF-10A were irradiated. The influence of irradiation on LPA receptor (LPAR) expression, ATX expression, and Interleukin (IL)-6 and IL-8 secretion was analyzed. Further, the effect of IL-6 and IL-8 on ATX expression of adipose-derived stem cells (ADSC) was investigated. Results: Irradiation increased ATX and LPAR2 expression in MDA-MB-231 cells. Additionally, IL-6 secretion was enhanced in MDA-MB-231, and IL-8 secretion in MDA-MB-231 and MDA-MB-468. Stimulation of ADSC with IL-6 and IL-8 increased ATX expression in ADSC. Conclusions: Targeting ATX or its downstream signaling pathways might enhance the sensitivity of triple-negative breast cancer cells to radiation. Further exploration of the interplay between irradiation, the ATX-LPA axis, and inflammatory cytokines may elucidate novel pathways for overcoming radioresistance and improving individual treatment outcomes.
CRIS-Team Scopus Importer:2024-10-11
Keywords: adipose-derived stem cells; ADSC; ATX; inflammatory mediators; LPA receptors; lysophosphatidate signaling

The Impact of Irradiation and Lipotransfer on Healthy Mammary Cells after Breast-Conserving Surgery - Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kengelbach-Weigand, Annika; Hauck, Theresa; Horch, Raymund E. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

The Impact of Technical Innovations and Donor-Site Mesh Repair on Autologous Abdominal-Based Breast Reconstruction—A Retrospective Analysis - Promny, Theresa; Huberth, Paula; Müller-Seubert, Wibke; Promny, Dominik; Cai, Aijia; Horch, Raymund E.; Arkudas, Andreas (Journal of Clinical Medicine, 2024)
Background: The aim of this study was to examine the potential benefit that may be achieved through the introduction of technical innovations and the incorporation of mesh for fascial donor site closure in uni- and bilateral autologous breast reconstruction with abdominal tissue. Methods: A retrospective single-center review of all breast reconstructions with a DIEP or MS-TRAM flap between January 2004 and December 2019 was performed. Donor and recipient site complications and operation times were evaluated before and after the implementation of coupler anastomoses, preoperative computed tomography angiography (CTA), indocyanine green (ICG) angiography, and the inclusion of mesh in donor site repair. Results: A total of 396 patients were included, accounting for 447 flaps. Operation time was significantly shorter in unilateral reconstructions after the implementation of CTA (p < 0.0001). ICG angiography significantly reduced the rates of partial flap loss (p = 0.02) and wound healing disorders (p = 0.02). For unilateral reconstructions, abdominal bulging or hernia was observed more often in MS1-TRAM flaps without synthetic mesh repair (p = 0.001), whereas conservatively treated seroma developed more frequently after mesh implantation (p = 0.03). Conclusions: Recent technological advancements developed over the past few decades have made a substantial impact on decreasing surgical duration and enhancing procedure safety.
CRIS-Team Scopus Importer:2024-05-03
Keywords: computed tomography angiography; coupler anastomoses; DIEP; indocyanine green angiography; MS-TRAM; perforator flaps; synthetic mesh

The third dimension in perforator mapping—Comparison of Cinematic Rendering and maximum intensity projection in abdominal-based autologous breast reconstruction - Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ströbel, Armin; May, Matthias; Binder, Johannes; Krautz, Christian; Ludolph, Ingo (Journal of Plastic Reconstructive and Aesthetic Surgery, 2022)
Background: Cinematic Rendering (CR) is a recently introduced post-processing three-dimensional (3D) visualization imaging tool. The aim of this study was to assess its clinical value in the preoperative planning of deep inferior epigastric artery perforator (DIEP) or muscle-sparing transverse rectus abdominis myocutaneous (MS-TRAM) flaps, and to compare it with maximum intensity projection (MIP) images. The study presents the first application of CR for perforator mapping prior to autologous breast reconstruction. Methods: Two senior surgeons independently analyzed CR and MIP images based on computed tomography angiography (CTA) datasets of 20 patients in terms of vascular pedicle characteristics, the possibility to harvest a DIEP or MS-TRAM flap, and the side of the flap harvest. We calculated inter- and intra-observer agreement in order to examine the accordance of both image techniques. Results: We observed a good inter- and intra-observer agreement concerning the type of flap and the side of the flap harvest. However, the agreement on the pedicle characteristics varies depending on the considered variable. Both investigators identified a significantly higher number of perforators with MIP compared with CR (observer 1, p<0.0001 and observer 2, p<0.0385). Conclusion: The current study serves as an explorative study, showing first experiences with CR in abdominal-based autologous breast reconstruction. In addition to MIP images, CR might improve the surgeon's understanding of the individual's anatomy. Future studies are required to compare CR with other 3D visualization tools and its possible effects on operative parameters.
CRIS-Team Scopus Importer:2022-03-11
Keywords: 3D visualization; Computed tomography angiography; DIEP; MS-TRAM

The Value of Negative-Pressure Wound Therapy and Flap Surgery in Hidradenitis Suppurativa – A Single Center Analysis of Different Treatment Options - Stumpfe, Maximilian; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ludolph, Ingo (Frontiers in Surgery, 2022)
Background: Hidradenitis suppurativa is manifested by painful abscesses and scarring of sweat glands. Axillary, inguinal and genital regions are mostly affected. Multiple options exist in the treatment of hidradenitis suppurativa. The aim of this retrospective, mono-center cohort study was to analyze the outcome of different treatment methods after radical excision of hidradenitis suppurativa. Methods: We retrospectively evaluated the treatment strategy and recurrence rate of hidradenitis suppurativa. We included all eligible patients of legal age between February 2003 and October 2021, with the diagnosis of Hidradenitis suppurativa and the necessity for surgical treatment. All patients with surgical treatment and direct wound closure by suture were excluded. Bacterial load and flora were analyzed for primary and secondary reconstruction in combination with negative-pressure wound therapy. Patient data were analyzed for recurrence rate and remission time according to different reconstructive techniques. Results: In 44 affected anatomical sites (n = 23 patients) we treated 15 patients with negative-pressure wound therapy. Bacterial load and flora were lower in the last wound swab of patients with multi-surgical procedures (22 localizations) compared to the first wound swab independent of the use of negative-pressure wound therapy. Wound closure, independent of a direct and multi-stage procedure was achieved by local fasciocutaneous flaps (n = 12), secondary intention healing (n = 7), secondary intention healing with buried chip skin grafts (n = 10), or split-thickness skin grafts (n = 15). Radical excision combined with split-thickness skin grafts showed the lowest recurrence rate in the follow-up (16%; n = 4). Conclusion: Radical excision of hidradenitis suppurativa as gold standard for surgical treatment combined with negative-pressure wound therapy as multi-stage procedures ultimately reduced bacterial load and flora in our study. The use of split-thickness skin grafts showed the lowest recurrence rate.
CRIS-Team Scopus Importer:2022-07-22
Keywords: acne inversa; bacterial burden; flap surgery; hidradenitis suppurativa; negative-pressure wound therapy

Topical negative-pressure wound therapy: emerging devices and techniques - Horch, Raymund E.; Ludolph, Ingo; Müller-Seubert, Wibke; Zetzmann, Katharina; Hauck, Theresa; Arkudas, Andreas; Geierlehner, Alexander (Expert Review of Medical Devices, 2020)
Introduction: The treatment of chronic wounds constitutes a massive financial burden to society and our health-care system. Therefore, efficient wound care is of great importance to all kinds of medical fields. The implementation and modification of negative-pressure wound therapy can be seen as a major improvement in wound healing. Many different NPWT applications evolved trying to address various wound etiologies. Areas covered: This review aims to give an overview of various NPWT applications, show its effects on wound healing, and discuss future modifications. Expert opinion: NPWT as a delivery device for cold plasma, growth factors, or targeted stem cells to the wound bed and the ability to monitor the inflammatory activity, bacterial load and wound healing factors can be seen as possible future steps to individualized wound care. In addition, it requires high-quality experimental studies to develop the ideal foam in terms of microstructure, pore size, and material properties.
CRIS-Team WoS Importer:2020-01-31

Vascular considerations in autologous breast reconstruction using DIEP or MS-TRAM flaps: Standard techniques, alternatives, and rescue strategies - Promny, Theresa; Arkudas, Andreas; Huberth, Paula; Horch, Raymund E. (Innovative Surgical Science, 2025)
Microsurgical breast reconstruction is an established method following mastectomy; however, various factors significantly influence the complication rate. This analysis evaluates the impact of vascular anastomosis techniques, previous surgeries, and radiotherapy on the success rate of microsurgical breast reconstruction. In a retrospective data analysis of 396 patients who underwent 447 flap procedures (single or bilateral microsurgical breast reconstruction) using tissue from the lower abdomen (either DIEP or MS-TRAM flaps), the type of venous and arterial anastomoses, the initial findings or surgical specifics at the thoracic recipient site and their influence on complications were examined. Anastomosing two veins per flap did not result in a significant reduction of major complications. Flap loss was significantly more common when standard venous anastomosis to the internal mammary vein was not used, underscoring their role as the preferred recipient vessels. No major complications were observed in patients receiving a caudal anastomosis to the internal mammary artery. Patients with prior radiotherapy exhibited an increased need for arterial revisions. All documented seromas and infections occurred in irradiated patients. A differentiated surgical plan that considers optimal anastomosis techniques, supercharging strategies, and individual risk factors is crucial to reducing complications. Further studies are needed to optimize patient-specific strategies.
CRIS-Team Scopus Importer:2025-06-06
Keywords: complications; cross over bypass; flap revision; supercharging; turbocharging